Self‐template synthesis of hierarchical porous carbon for supercapacitors based on bituminous coal. (6th September 2020) - Wang, Xing; Qin, Zhihong; Yang, Xiaoqin; Chen, Qiang; Lin, Zhe
Summary: We develop a unique self‐template method to synthesize hierarchical porous carbons (HPCs) by co‐activation of heavy component (HC) and dense medium component (DMC) separated from bituminous coal. HC and DMC are obtained by employing the mixture solvent (CS2 /N‐methyl‐2‐pyrrolidone) and deionized water as extractant and back extractant to separate bituminous coal. The plentiful kaolinite [Al2 (Si2 O5 ) (OH)4 ] in the HC produce Natrolite (K) (K2 Al2 Si3 O10 2H2 O) during the activation process, which can serve as self‐template to prepare HPCs. Moreover, the addition of asphalt‐like DMC allows the templates to be better utilized. Effect of the remixture ratio of DMC/HC on HPCs' porous structures and electrochemical properties are studied in detail. The optimal sample (HPC‐0.4) displays an ultrahigh surface area (3851 m 2 g −1 ), appropriate hierarchically system and excellent conductivity. When applied to supercapacitors, HPC‐0.4 delivers a large capacity of 436 F g −1 at 0.1 A g −1 in alkaline electrolyte, and maintains 212 F g −1 at 10 A g −1 . This self‐template strategy paves a practical route to construct applicable porous carbons for supercapacitors from low‐cost high‐minerals coal. Abstract : A unique self‐template strategy was presented to construct hierarchical porous carbon based on separation and remixture of bituminous coal. The as‐obtained carbon delivers an ultrahigh specific area (3851 m 2 g −1 ) and appropriate hierarchically system. The assembled supercapacitors exhibited high capacitance (436 F g −1 at 0.1 A g −1 ), good rate performance (212 F g −1 at 10 A g −1 ) and cycling stability (92.7% retention after 6000 cycles).